"The effects of cancer on a family are way beyond the person who's had it": The experience and effect of a familial cancer diagnosis on the health behaviours of family members. (April 2021) - McKeague, Beth; Maguire, Rebecca
Abstract: Purpose: People who are first-degree relatives of cancer patients are at an increased risk of developing cancer themselves. Despite this, relatives of cancer patients do not always make beneficial changes to their health behaviours. This study aimed to answer the following questions: (1) do the health behaviours of people who are first-degree relatives of cancer survivors change following cancer diagnosis, and if so, how, and why, (2) what motivations/barriers exist for first-degree relatives when seeking to engage with health promoting behaviours, and (3) what do first-degree relatives believe healthcare organisations can do to improve uptake of healthy lifestyle changes. Method: Nine biological first-degree relatives of cancer survivors living in Ireland (6 children, 2 siblings, 1 parent) participated in semi-structured interviews which were later thematically analysed. Results: Findings revealed four superordinate themes: Being Conscious/Aware, Limited Lifestyle Changes, Psychosocial Consequences of Experience, and Unmet Needs, with each of these themes having two to three subordinate themes. Patient and public involvement emphasised Unmet Needs, including needs for information and family support, as the theme that was most reflective of participants' lived experience. Conclusions: Results suggest that while family members tend not to change their lifestyle behaviours following cancer diagnosis, they do seem to make changes to their medical behaviours. Additionally, they can be negatively impacted by the experience in several other ways. Identifying means of support will allow relatives to cope better post diagnosis. Highlights: People who have a relative with cancer are more likely to get cancer themselves. Those with a family history of cancer often make limited behavioural changes. Limited changes occur due to effort required, perceived existing health, and more. Cancer negatively impacts on relatives' overall wellbeing and family relationships. Better support for relatives could help them cope better after the diagnosis.